The effect of information on gender differences in competitiveness: experimental evidence - Seda Ertac; Balázs Szentes (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
An important line of recent literature has found gender differences in attitudes toward competition, with men being more likely to choose competitive incentive schemes, even when factors such as ability and risk aversion are controlled for. This paper examines the effect of information on the gender gap in tournament entry. We present experimental evidence that the competitiveness difference between men and women declines significantly when individuals are given performance feedback before making their incentive scheme choice. The result suggests that policies that reduce uncertainty can reduce the gender gap in tournament entry.
Keywords: C91; D83; J16; 330; experiments; gender; competition; information; incentive schemes; Geschlechterdiskriminierung; Arbeitsmarktdiskriminierung; Führungskräfte; Leistungsbeurteilung; Vergütungssystem; Test